Synthesis and Characterization of Glycosides - Brito-Arias, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This second edition is a short and comprehensive study on the best known approaches for preparing the main types of glycosides. It covers synthetic pathways of challenging glycosides known as antiviral or antineoplastic drugs, and synthetic substrates used for enzymatic detection, including those used for detection of gene markers in plant biotechnology. The author pays special attention to the structural characterization of glycosides and provides the basic tools for the structural assignment through NMR, X-Ray and mass spectra techniques. The book also covers strategies for preparation of antiviral and antineoplastic drugs included in a drug design course.
Introduction -- O-Glycoside Formation -- N-glycosides -- Nucleotide Mimetics -- C-glycosides -- Glycoconjugates -- Hydrolysis of Glycosides -- Nuclear Magnetic Resonance of Glycosides -- X-Ray Diffraction of Glycosides -- Mass Spectrometry of Glycosides -- Docking studies of Glycosides -- Index.
Keywords: Chemistry, Organic; Biotechnology; Chemistry, Technical; Medicinal chemistry; Analytical chemistry; Organic Chemistry; Biotechnology; Industrial Chemistry; Medicinal Chemistry; Analytical Chemistry